2018
DOI: 10.1021/acs.inorgchem.8b00773
|View full text |Cite
|
Sign up to set email alerts
|

Site Occupation of Eu2+ in Ba2–xSrxSiO4 (x = 0–1.9) and Origin of Improved Luminescence Thermal Stability in the Intermediate Composition

Abstract: Knowledge of site occupation of activators in phosphors is of essential importance for understanding and tailoring their luminescence properties by modifying the host composition. Relative site preference of Eu for the two distinct types of alkaline earth (AE) sites in BaSr EuSiO ( x = 0-1.9) is investigated based on photoluminescence measurements at low temperature. We found that Eu prefers to be at the 9-coordinated AE2 site at x = 0, 0.5, and 1.0, while at x = 1.5 and 1.9, it also occupies the 10-coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…As displayed in Figure B, the emission intensity at 423 K was about 76% of the initial intensity at room temperature which demonstrated that the NaSrLa(MoO 4 )O 3 :0.04Er 3+ possessed excellent thermal stability. Besides, to further clarify the thermal stability of NaSrLa(MoO 4 )O 3 : x Er 3+ phosphors, the activation energy was analyzed using the following expression:lnI0I-1=lnA-ΔEitalickT,where I 0 and I present initial emission intensity and the emission intensity at different temperatures ( T ), respectively. Δ E , k , and A are the activation energy, Boltzmann constant and coefficient, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As displayed in Figure B, the emission intensity at 423 K was about 76% of the initial intensity at room temperature which demonstrated that the NaSrLa(MoO 4 )O 3 :0.04Er 3+ possessed excellent thermal stability. Besides, to further clarify the thermal stability of NaSrLa(MoO 4 )O 3 : x Er 3+ phosphors, the activation energy was analyzed using the following expression:lnI0I-1=lnA-ΔEitalickT,where I 0 and I present initial emission intensity and the emission intensity at different temperatures ( T ), respectively. Δ E , k , and A are the activation energy, Boltzmann constant and coefficient, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The DFT total energies of Model-1 and Model-2 revealed that Mn 2+ strongly preferred to be at the Mg(1) site over the Mg(2) site (by 1.14 eV). 25 In summary, it is proved that Mn 2+ may have a preference for the dodecahedral sites with eight coordination in YMAS:Ce 3+ ,Mn 2+ . However, so far, there are few characterization methods to directly and clearly detect the chemical environment of Mn 2+ .…”
Section: Papermentioning
confidence: 85%
“…Third, the Debye temperature (Θ D ) calculation usually identifies crystal structure rigidity, which is usually determined with a quasiharmonic model. , In order to screen matrixes with stable physicochemical properties and excellent environmental stability, the Debye temperature and effective mass analysis take effect. Finally, optical properties and dynamics calculation can give detailed luminescent properties prediction for involved phosphors.…”
Section: High-throughput Calculation and Crystal Structure Design To ...mentioning
confidence: 99%